2018
DOI: 10.1186/s13613-018-0355-0
|View full text |Cite
|
Sign up to set email alerts
|

Response to different furosemide doses predicts AKI progression in ICU patients with elevated plasma NGAL levels

Abstract: BackgroundFurosemide responsiveness (FR) is determined by urine output after furosemide administration and has recently been evaluated as a furosemide stress test (FST) for predicting severe acute kidney injury (AKI) progression. Although a standardized furosemide dose is required for FST, variable dosing is typically employed based on illness severity, including renal dysfunction in the clinical setting. This study aimed to evaluate whether FR with different furosemide doses can predict AKI progression. We fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 49 publications
1
44
0
1
Order By: Relevance
“…The diagnostic criteria for AKI were different in the eleven enrolled studies. Five of the studies (Elsaegh, 2018;Lumlertgul, 2018;Martínez, 2016;Matsuura, 2018;Vairakkani, 2019) [14][15][16][17][18] used the Kidney Disease: Improving Global Outcomes (KDIGO) criteria [19]. Other studies used the Acute Kidney Injury Network (AKIN) criteria [20].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…The diagnostic criteria for AKI were different in the eleven enrolled studies. Five of the studies (Elsaegh, 2018;Lumlertgul, 2018;Martínez, 2016;Matsuura, 2018;Vairakkani, 2019) [14][15][16][17][18] used the Kidney Disease: Improving Global Outcomes (KDIGO) criteria [19]. Other studies used the Acute Kidney Injury Network (AKIN) criteria [20].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Vairakkani, 2019) [16][17][18] used the KDIGO stage 3 AKI as primary outcome. Two studies (Elsaegh, 2018; Saber, 2018) reported primary composite outcome consist of AKI progression and RRT [14,24].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations